2017
DOI: 10.1002/14651858.cd006364.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative antibiotics for prevention of acute endophthalmitis after cataract surgery

Abstract: Background Endophthalmitis is a severe inflammation of the anterior or posterior (or both) chambers of the eye that may be sterile or associated with infection. It is a potentially vision-threatening complication of cataract surgery. Prophylactic measures for endophthalmitis are targeted against various sources of infection. Objectives To evaluate the effects of perioperative antibiotic prophylaxis for endophthalmitis following cataract surgery compared with no prophylaxis or other form of prophylaxis. Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 73 publications
1
78
0
3
Order By: Relevance
“…While the debate regarding the safety and efficacy of using IC antibiotic prophylaxis continues, a recent Cochrane review[ 56 ] analyzed studies that had been published through December 2016 and concluded that the 2007 ESCRS study demonstrated the efficacy of using IC antibiotics for reducing endophthalmitis. However, the antibiotic of choice may differ based on the clinical setting.…”
Section: Resultsmentioning
confidence: 99%
“…While the debate regarding the safety and efficacy of using IC antibiotic prophylaxis continues, a recent Cochrane review[ 56 ] analyzed studies that had been published through December 2016 and concluded that the 2007 ESCRS study demonstrated the efficacy of using IC antibiotics for reducing endophthalmitis. However, the antibiotic of choice may differ based on the clinical setting.…”
Section: Resultsmentioning
confidence: 99%
“…Male gender and DM have been described as patient-associated pre-operative risk factors for post cataract surgery endophthalmitis [ 11 ]. Based on previous studies and meta-analysis, prophylaxis with intracameral injection of cefuroxime reduce the rate of post cataract surgery endophthalmitis [ 27 29 ]. Because our patients underwent cataract surgery in other ophthalmologic clinic, we were not aware of the use of prophylaxis antibiotic during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 5 Although several studies of intracameral injection have reported reduced rates of endophthalmitis, compared with no antibiotic injection, the choice of antibiotic has varied, including moxifloxacin, vancomycin, and cefuroxime, and the ideal choice of antibiotic agent remains unclear. 4 , 12 Additionally, identified barriers to provider uptake have included a lack of commercially available preparations and concerns regarding dilution errors and risk of contamination when compounding the drugs for required doses. Ophthalmologists in the US have indicated that intracameral antibiotic use would likely increase if a single-dose vial was commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Although perioperative intracameral antibiotic administration was controversial in the past, a growing body of evidence has demonstrated a significant reduction in the incidence of endophthalmitis when this technique is used. 2 4 In addition, the safety of intracameral injection of antibiotics following cataract surgery has been demonstrated by evaluating parameters, including anterior chamber reaction, corneal thickness, and corneal endothelial density. 5 …”
Section: Introductionmentioning
confidence: 99%